IDENTIFIKASI KINERJA KEUANGAN PERBANKAN TERBAIK DI ASEAN (Studi Komparatif: Indonesia, Thailand, Philipine) (Proceeding SENDI_U, 2015)
ASEAN Economic Community (AEC) started walking,state-owned commercial banking industry has an importantrole on the passage of the macro economy in the ASEAN countries in this regard; Indonesia, Philipine, Thailand,Thailand, the Philippines, Brunei Darussalam, Cambodia, Laos, Myanmar and Vietnam. In this study the authorscompare the performance of the best banking financial statements in ASEAN are: Indonesia (Bank Mandiri Tbk.),Thailand (Siam Commercial Bank) and Philippine (Banco de Oro Unibank) with indicators: Capital Risk, AssetQuality, Operating Efficiency, Liquidity Risk, Profitabilty and Growth. Using the Kruskal-Wallis statistical test -Mann Whitney U with six bank financial performance measurement tool. The data series are taken from thefinancial statements 2009 - 2013 derived from the respective websites of government banks concerned; BankMandiri Tbk. (Indonesia), Siam Commercial Bank (Thailand), Banco de Oro Unibank (Philippine), the central bankand the stock market in ASEAN countries and international financial institutions. Hypothesis testing for normal datainclude indicators: Capital Risk or capital adequacy ratio (CAR), Asset Quality or non-performing loan (NPL),Operating Efficiency or employee expenses to total assets (BOPO), Liquidty Risk or loan-to-deposit ratio ( LDR),Profitability or return on assets (ROA) and return on equity (ROE) and Growth or assets growth rate (AGR). Theresults showed that the ratio of the entire Indonesian banking financial indicators with Thailand and Philippine thereare significantly different and there are not significant. The average ratio-banking financial ratio Indonesiangovernment is better; NPLs, ROA and ROE otherwise CAR, ROA, LDR and AGR less well when compared withThailand and Philippine. The contribution of this study is expected to provide input for the managerial khbususnyabanking Indonesian government to further improve the quality and quantity of performance. Likewise for otherresearchers in order to increase the interest to do a more in-depth research about government banking in ASEAN.Keywords: Financial ratios, financial performance, ASEA.